High-school dropouts and transitory labor market shocks: The case of the spanish housing boom - Ainhoa Aparicio (Institute for the Study of Labor (IZA), 2010)
This paper addresses the implications of transitory changes in labor market conditions for low versus high educated workers on the decision to acquire education. To identify this effect, I use the improvement in the labor market prospects of low educated workers motivated by the increases in employment and wages in the construction sector during the recent housing boom. The estimation strategy is based on the fact that changes in the labor market driven by the construction sector affect only men. Increases in construction activity are found to increase men's propensity to drop out of high-school, relative to women. According to this finding, policies promoting education should strengthen when in the presence of transitory shocks in the labor market that make dropping out more attractive.
urn:nbn:de:101:1-201010133373
Keywords: J24; J22; I20; L74; 330; high-school dropout; housing boom; Spain